More on Fixed Point Theorem of $\{a,b,c\}$-Generalized Nonexpansive Mappings in Normed Spaces (Analysis in Theory and Applications, 2013)
Let $X$ be a weakly Cauchy normed space in which the parallelogram law holds, $C$ be a bounded closed convex subset of $X$ with one contracting point and $T$ be an $\{a,b,c\}$-generalized-nonexpansive mapping from $C$ into $C$. We prove that the infimum of the set $\{\| x-T(x) \|\}$ on $C$ is zero, study some facts concerning the $\{a,b,c\}$-generalized-nonexpansive mapping and prove that the asymptotic center of any bounded sequence with respect to $C$ is singleton. Depending on the fact that the $\{a,b,0\}$-generalized-nonexpansive mapping from $C$ into $C$ has fixed points, accordingly, another version of the Browder's strong convergence theorem for mappings is given.
Keywords: Fixed point theorem; $\{a; b; c\}$-generalized-nonexpansive mapping; asymptotic center; Browder's strong convergence Theorem.